Simulated Response of a Tissue-equivalent Proportional Counter on the Surface of Mars. Issue 4 (October 2015) - Northum, Jeremy D.; Guetersloh, Stephen B.; Braby, Leslie A.; Ford, John R.
Abstract : Abstract: Uncertainties persist regarding the assessment of the carcinogenic risk associated with galactic cosmic ray (GCR) exposure during a mission to Mars. The GCR spectrum peaks in the range of 300 MeV n −1 to 700 MeV n −1 and is comprised of elemental ions from H to Ni. While Fe ions represent only 0.03% of the GCR spectrum in terms of particle abundance, they are responsible for nearly 30% of the dose equivalent in free space. Because of this, radiation biology studies focusing on understanding the biological effects of GCR exposure generally use Fe ions. Acting as a thin shield, the Martian atmosphere alters the GCR spectrum in a manner that significantly reduces the importance of Fe ions. Additionally, albedo particles emanating from the regolith complicate the radiation environment. The present study uses the Monte Carlo code FLUKA to simulate the response of a tissue-equivalent proportional counter on the surface of Mars to produce dosimetry quantities and microdosimetry distributions. The dose equivalent rate on the surface of Mars was found to be 0.18 Sv y −1 with an average quality factor of 2.9 and a dose mean lineal energy of 18.4 keV μm −1 . Additionally, albedo neutrons were found to account for 25% of the dose equivalent. It is anticipated that these data will provide relevant starting points for use in future risk assessment and mission planning studies.